TINJAUAN PENDIDIKAN SOSIAL DAN HUKUM TERHADAP KEKERASAN DALAM RUMAH TANGGA - Novianty Djafri (Jurnal Inovasi, 2008)
Lack of education which is ekslusif for husband / wife spouse can create hardness in considered at household of Crime Hidden which have eaten quite a lot victims from various society circle. This matter earn happened in so many form and because of various factor. As a result, grief do not only experienced of by just wife, but also the child of because in household of course do not only there are just wife and husband but also there are possible children see directly or minimize heard the happening of hardness action in household. Hardness in household can hinder attainment of mashlahat concerning in with process and household education of people regenerasi. Therefore, very need isn't it punish Islam capable to become umbrella protecting to be looked after and reached him of mashlahat.